Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) in Water of an Abandoned Borrowed Pit with Wood-dust Deposit, Port Harcourt, Nigeria - Iyama, William Azuka; Edori, Simeon Onisogen; Okwuchukwu, Chika; Emejuru, Woroma Stella (European Journal of Applied Sciences, 2022)
The incidence of borrow pit pollution is a common phenomenon all over the world and Polycyclic aromatic hydrocarbons (PAHs) present in the environment are on the increase. Water samples from wood-dust effluent points at Egbelu, Port Harcourt were collected and analyzed for PAHs concentration. The analysis was achieved after extraction with Dichromethane and n-hexane in a Soxhlet extractor while Gas Chromatography mass spectrometry was used to separate and identify the components of PAHs in the water samples. The results obtained showed the presence of 2-3, 4 and 5-member ring priority PAHs from the borrow pit, while others were not detected from any of the locations examined. Different classifications showed that the mean concentration value for 2-3, 4 and 5 member rings were 0.132±0.00381, 0.235±0.00381, and 0.192±0.00436 mg/L respectively. In all, eight priority PAHs were detected (Benzo (a) Pyrene, Benzo (k) Fluoranthene, Indo (1,2,3, c-d) Pyrene, Dibenzo (a,h) Anthracene, Benzo(g,h,i) Naphthalene, Flourene and Anthracene. The Mean concentration of samples also showed Ao to be the highest in PAHs concentration while Bo is the lowest. Thus indicating the impact of wood dust on PAHs with only pyrogenic source of contamination. Authorities involved with administration, management and enforcement of contaminants and pollutants on dumping sites should channel their efforts to curb the incidence of outburst of PAHs pollution in the future and fishes from the same source be studied to show the levels of absorption.